Protocol for a validation study of the translated stapesplasty outcome test 25 for measurement of disease-specific quality of life in Dutch patients with otosclerosis - Esther E Blijleven; Hans G X M Thomeer; Robert Stokroos; Inge Wegner (BMJ Open)
Introduction Otosclerosis is a common cause of acquired conductive hearing loss and can be treated using hearing aids or surgically. Surgical success rates or surgical results are usually reported using pure-tone audiometric thresholds and/or speech discrimination scores. Audiometric results and patient-reported quality of life after stapes surgery do not seem to correlate well. It is therefore our opinion that health-related quality of life measurements should be implemented as an additional outcome measure after stapes surgery. So far, there is a lack of a valid, reliable and clinically feasible measuring tool for determining health-related quality of life in Dutch patients with otosclerosis who undergo stapes surgery.Methods and analysis A prospective validation study was designed to translate and validate the disease-specific Stapesplasty Outcome Test 25 (SPOT-25) in a population of Dutch patients with otosclerosis who undergo primary stapes surgery. A total of 125 patients with otosclerosis who will be undergoing primary stapes surgery and 50 healthy controls will be included. The patients with otosclerosis will fulfil several questionnaires preoperatively, 6 to 8 weeks postoperatively and 8 to 10 weeks postoperatively with a 2-week interval between the postoperative administrations. The patients’ audiometric results, which are measured routinely before and after undergoing primary stapes surgery, will also be used. The healthy controls will fulfil the translated SPOT-25 once. First, the original SPOT-25 will be translated from German to Dutch in a six-step process. Second, the translated SPOT-25 will be pilot-tested in a subset of patients. Lastly, validity, reliability and responsiveness of the translated SPOT-25 will be analysed.Ethics and dissemination The research protocol was approved by the Institutional Review Board of the University Medical Center Utrecht (protocol 18–768/C; V.1, November 2018). Initially, we planned to include 50 patients. At a later stage we decided to increase the sample size to 100 patients. We notified the Institutional Review Board of this change to the protocol. The trial results will be disseminated through peer-reviewed medical journals and presented at scientific conferences.Trial registration number NL7586.